Polymorphism of LRP5 gene and emphysema severity are associated with osteoporosis in Japanese patients with or at risk for COPD. Issue 2 (12th November 2014) - Chubachi, Shotaro; Nakamura, Hidetoshi; Sasaki, Mamoru; Haraguchi, Mizuha; Miyazaki, Masaki; Takahashi, Saeko; Tanaka, Kyuto; Funatsu, Yohei; Asano, Koichiro; Betsuyaku, Tomoko; the Keio COPD Comorbidity Research (K‐CCR) Group
Abstract Background and objective Osteoporosis is an important systemic comorbidity of chronic obstructive pulmonary disease (COPD). However, neither its mechanisms nor its risk factors have been fully elucidated. With regard to genetic factors, low‐density lipoprotein receptor‐related protein 5 (LRP5) A1330V is known to be associated with osteoporosis in the general population, but the influence of this polymorphism in COPD is unknown. The aim of this study was to investigate the potential risk factors of COPD‐related bone loss and fracture. Methods Keio University and affiliated hospitals have enrolled an observational cohort to investigate the management of COPD comorbidities. To assess risk factors for osteopenia and osteoporosis, bone mineral density (BMD) of the hip and lumbar spine, presence of vertebral fracture, quantitative data on emphysema and airway wall on computed tomography, as well as LRP5 genotype were analysed in patients with or at risk for COPD (n = 270). Results The percentage of subjects with osteoporosis (T‐score ≤ −2.5), osteopenia (T‐score between −1 and −2.5) and a normal BMD (T‐score ≥ −1) was 15.2%, 35.9% and 48.9%, respectively. T‐score was significantly decreased in subjects with LRP5 TT genotype (n = 15) compared with that in those with CC/CT genotype (n = 255) (−1.83 vs. −0.98, P = 0.0167). On multivariate logistic regression analysis, female gender (odds ratio (OR) 10.4; P < 0.0001), severe emphysema (OR 2.3; P = 0.013) and LRP5 TT genotype (OR 3.7; P = 0.031) independently increased the risk of osteopenia/osteoporosis. Conclusions This study confirmed the complex pathophysiology of COPD‐related osteoporosis, including the influence of gender, clinical phenotype and genetic factors.